The assessment [videorecording (DVD)] - Garfath-Cox, Nell; Thomas, Dave (Screenwriter); Donnelly, John (Screenwriter); Olsen, Elizabeth, 1989-; Vikander, Alicia, 1988-; Patel, Himesh, 1990-; Varma, Indira; Pinnock, Nicholas, 1973-; Ritchie, Charlotte, 1989-; Harvey, Leah; Driver, Minnie; Levienaise-Farrouch, Emilie; et al. (Magnolia Home Entertainment, 2025)
In the near future where parenthood is strictly controlled, a couple's seven-day assessment for the right to have a child unravels into such a psychological nightmare that they begin to question the basis of their world.